What can be done to impact respiratory inhaler misuse: exploring the problem, reasons, and solutions - Volerman, Anna (Expert Rev Respir Med, 2020)
INTRODUCTION: Respiratory inhalers, when used correctly, provide critical treatments for managing pulmonary conditions. However, many patients misuse inhalers, negatively affecting disease control, quality of life, healthcare utilization, and costs. Numerous factors are associated with misuse and are nested within four levels of influence: individual, interpersonal, organizational/institutional, and policy. AREAS COVERED: This review analyzed published literature and identified the most salient factors at each level of this socio-ecological framework. English language articles from any year were identified from PubMed, Google Scholar, and Embase databases. Misuse exists across clinical settings, patient populations, and device types. Several potential solutions are highlighted. Published interventions to improve inhaler technique have utilized handouts, in-person, virtual, and biofeedback approaches both inside and outside of healthcare settings with varied effectiveness. However, some interventions have superior effectiveness for improving technique and reducing acute care utilization. EXPERT OPINION: To robustly address inhaler misuse, future solutions should focus on multi-level approaches to account for the myriad of factors contributing to inhaler misuse. Solutions should also streamline inhaler equipment, identify innovative technology-based solutions, support collaborations across healthcare and non-healthcare settings, and ensure reimbursement to healthcare professionals for inhaler education. Rigorous research studies must be funded and supported to identify and disseminate solutions.